2016
DOI: 10.1111/jvp.12298
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of methocarbamol and phenylbutazone in exercised Thoroughbred horses

Abstract: Methocarbamol (MCBL) is commonly used in performance horses for the treatment of skeletal muscle disorders. Current regulatory recommendations for show horses and racehorses are based on a single oral dose of 5 g, although doses in excess of this are often administered. The goal of the current study was to characterize the disposition of MCBL following higher dose administration and administration in combination with another commonly used drug in performance horses, phenylbutazone (PBZ). Exercised Thoroughbred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…The volume of distribution at steady state and clearance of PBZ in this study are in agreement with previous reports 9,17‐19 . Interestingly, in this study PBZ metabolite concentrations were quantifiable for a prolonged period of time, compared with a previous reports conducted by this laboratory 9 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The volume of distribution at steady state and clearance of PBZ in this study are in agreement with previous reports 9,17‐19 . Interestingly, in this study PBZ metabolite concentrations were quantifiable for a prolonged period of time, compared with a previous reports conducted by this laboratory 9 .…”
Section: Discussionsupporting
confidence: 93%
“…15,16 If the relative binding affinity of PBZ for plasma proteins is higher, the increase The volume of distribution at steady state and clearance of PBZ in this study are in agreement with previous reports. 9,[17][18][19] Interestingly, in this study PBZ metabolite concentrations were quantifiable for a prolonged period of time, compared with a previous reports conducted by this laboratory. 9 One of the most likely explanations for the differences in detection times between studies is analytical assay sensitivity; however, as the assay used in this study was the same as that used in the previously published study by this laboratory, 9 this would not appear to be the only reason.…”
Section: F I G U R Ementioning
confidence: 69%
“…The European Horseracing Scientific Liaison Committee advises a 168‐hour (6‐day) detection time for PBZ, the same detection time as the Fédération Équestre Internationale (FEI) . While its use is prevalent, and it has been well studied in the horse, there is a limited number of comprehensive published studies describing blood and urine concentrations and the pharmacokinetics of this drug and its metabolites in a large population of young horses that are suitable for the establishment of regulatory recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…The author has found that these medications can bring some relief in such instances. Methocarbamol is a centrally acting skeletal muscle relaxant, labelled to reduce muscular spasms [104], and is commonly used as a first-choice drug for these cases. There is a very large dose range for intravenous use of 4.4-55.0 mg/kg.…”
Section: Muscle Relaxantsmentioning
confidence: 99%